The Relationship of T Helper-2 Pathway Components Interleukin-4, Interleukin-10, Immunoglobulin E, and Eosinophils with Prognostic Markers in Non-Hodgkin Lymphoma: A Case-Control Study - Güler, Nil (Turk J Haematol, 2014)
Objective: Increased risk for non-Hodgkin lymphoma (NHL) is associated with infections and environmental agents. We hypothesized that these factors chronically trigger the T helper-2 (Th2) pathway and result in lymphoma. We investigated the role of the Th2 pathway by exploring the relationships between components of the Th2 pathway, interleukin (IL)-10, IL-4, immunoglobulin E (IgE), and eosinophils, and prognostic markers of NHL. Materials and Methods: Thirty-one NHL patients and 27 healthy controls were enrolled. IL-10, IL-4, IgE, and eosinophils were measured. IL-4 and IL-10 were analyzed with the enzyme amplified sensitivity immunoassay method. Results: High IL-10 levels were correlated with several poor prognostic features, short early survival, and lymphopenia. There was a positive correlation between albumin and IL-4 levels and a negative correlation between IL-10 and albumin. There was no relationship related with eosinophils and IgE. We found remnant increased IL-4, which could be a clue for the triggering of the Th2 pathway in the background. Conclusion: There is a need for differently designed studies to detect the place of the Th2 pathway in NHL.